Factorise p3-125q3 +1+15pq

Asked by Pranav Gupta | 7th Sep, 2012, 10:48: PM

Expert Answer:

p3 - 125q3 + 1 + 15pq

= (p)3 + (-5q)3 + 13 -3 × p × (-5q) × 1

=  [p + (-5q) + 1] [p2 + (-5q)2 + 12 - p × (-5q) - (-5q) × 1 - 1 × p]

[It is because of a3 + b3 + c3 -3abc = (a + b + c) (a2 + b2 + c2 - ab - bc - ca)]

=  (p -5q + 1) (p2 + 25q2 + 1 + 5pq + 5q - p)

Answered by  | 8th Sep, 2012, 01:18: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.